Penerapan Akuntansi Publik dalam Pertanggungjawaban Kinerja Instansi Pemerintah di Kantor Koperasi Usaha Kecil Kabupaten Mandailing Natal - Abdul Nasser Hasibuan; Ali Hardana; Lismawati Hasibuan; Try Wahyu Utami; Sulaiman Efendi Siregar (Jurnal Simki Economic, 2023)
The term governance is actually an old term that was re-popularized by the World Bank in 1992 in its report entitled Governance and Development. The World Bank underscored that governments are the source of development failures. A great government will result in bad governance. "Big government is bad governance". The purpose of this study is to understand implementation strategies regarding accountability and accountability, as well as their implications for how public sector employees work at the Mandailing Natal district office. Data analysis uses a descriptive methodology to gather, transform, classify, interpret, and analyze data to provide clear and accurate information about the problem. The four pillars of the strategic planning process are vision (foresight), consistency, decentralization, transparency, responsiveness, professionalism, and competence. The criteria that writers have in mind when reviewing and analyzing the work of the Representative Office Mandailing Natal Corporation include validity and rigor, professionalism, and a commitment to helping others. Consistency, accuracy, fairness, transparency, focus, and dependability are the bots that are mentioned in the Reporting.